Construction of Recombinant Yeast Expressing Thermo-Stable Enzyme for Efficient Bioethanol Production from Woody Biomass - Abu Saleh, Ahmed; Seiya, Watanabe; Sinin, Hamdan; Tsutomu, Kodaki; Keisuke, Makino (FKKKSA, 2014)
Xylitol dehydrogenase from Pichia stipitis (PsXDH) is one of the key enzymes for the bioethanol fermentation system from biomass sugars. Previously, the C4 mutant (S96C/S99C/Y102C) was constructed with enhanced thermostability by introduction of structural zinc. A high thermostability of PsXDH was obtained by subsequent site-directed mutagenesis of the structural zinc-binding loop. In this study, effects of thermostabilization of xylitol dehydrogenase (XDH) from Pichia stipitis on fermentation of xylose to ethanol were estimated using a recombinant Saccharomyces cerevisiae expressing together with a native xylose reductase (XR) from P. stipitis. The mutated XDH performed the similar enzyme properties in S. cerevisiae cells, compared those in vitro. The significant enhancement was found in Y-C4 strain, 51% decrease of unfavorable xylitol excretion with 19% increased ethanol production, when compared with the reference strain expressing the wild–type XDH.